The Relationship Between Financial Innovation And Cost Efficiency In China’s Commercial Banking - Feng, Zehao (2018)
This study uses a stochastic frontier analysis to examine the relationship between financial innovation and bank cost efficiency. The dataset consists of 171 observations from 37 commercial banks in China from 2011 to 2017. The purpose of this investigation is to provide several implications for bankers and policy-makers, which may benefit the development of China’s commercial banking sector. Firstly, the investigation of the averaged cost efficiency presents a fluctuating upward trend in China’s commercial banking sector from 0.8 to 0.85 between 2011 and 2017. Then, there are five indicators includes investment income, fee and commission income, employees with the high education degree, staff training expense and ownership concentration to reflect different types of financial innovation. The empirical result indicates that the increase in investment income, fee and commission income, the percentage of high-level employees and staff training expense will lead to the cost efficiency improvement. However, the high ownership concentration may have the adverse effect on cost efficiency. Overall, the financial innovation is beneficial to the improvement of bank cost efficiency. Finally, there are several recommendations for the long-term development of commercial banks: 1. establishing innovation consciousness. 2. developing innovative business. 3. improving human capital quality. 4. developing the financial technology. 5. promoting system reform.